Enhancing students' data literacy through the hybrid creative problem-solving laboratory (HCP-Lab) in physics experiments courses - Rizki Zakwandi; Alfiansah Sandion Prakoso; Ika Mustika Sari; Asep Akmal Fadia Nurhalim; Najmi Hiyan Fathinah; Rahma Alliya Aqquilla; Duden Saepuzaman; Desy Purwasih (EDUSAINS, 2026)
Physics learning is inherently grounded in inquiry-based processes, particularly through experimental activities that engage students in observing physical phenomena. These observations are subsequently analyzed and interpreted to develop conceptual understanding, making data literacy an essential competency in physics education. However, many schools face challenges in conducting laboratory activities due to the high costs associated with procuring and maintaining experimental equipment. Moreover, conventional laboratory practices often fail to explicitly integrate data literacy as a core component of the learning process. To address these challenges, this study proposes an alternative approach that utilizes readily available devices, such as smartphones, as experimental tools. As a pilot project, a Hybrid Creative Problem-Solving Laboratory (HCP-Lab) model was developed and implemented to enhance students’ data literacy skills in an introductory physics laboratory course. The study adopted Plomp’s Educational Design Research framework and involved 28 first-year physics students, divided into two classes (15 students in Class A and 13 students in Class B). Data was collected over an eight-week period using data literacy assessments, student development observation sheets, and portfolio evaluations. Quantitative data were analyzed using descriptive and inferential non-parametric statistical techniques, while qualitative data were examined using NVivo software. The findings indicate that the HCP-Lab model effectively supported the development of students’ data literacy skills, with observable improvements throughout the intervention. Students demonstrated notable progress in data processing, interpretation, and evidence-based conclusion drawing. Statistical analysis revealed a significant difference between pre- and post-intervention data literacy performance (p < .05). In addition, students reported that the HCP-Lab model provided a novel, engaging, and comprehensive laboratory learning experience. These findings suggest that the HCP-Lab model offers a viable alternative for physics laboratory instruction, particularly in educational settings with limited access to conventional laboratory equipment, while simultaneously fostering essential data literacy competencies.